Application and optimization of reference change values for Delta Checks in clinical laboratory. Issue 12 (30th August 2020) - Hong, Jinyoung; Cho, Eun‐Jung; Kim, Hyun‐Ki; Lee, Woochang; Chun, Sail; Min, Won‐Ki
Abstract: Background: Delta check is a patient‐based QC tool for detecting errors by comparing current and previous test results of patient. Reference change value (RCV) is adopted in guidelines as method for delta check, but the performance is not verified. We applied RCV‐based delta check method to patients' data and modified for application. Materials and methods: Reference change value were calculated using results of internal QC materials and biological variation data. Test results of 17 analytes in inpatients, outpatients, and health examination recipients were collected. The detection rates of currently used delta check method and those of RCV‐based method were compared, and the methods were modified. Results: Reference change value‐based method had higher detection rates compared to conventional method. Applied modifications reduced detection rates. Removing the pairs of results within reference interval reduced detection rates (0.42% ~ 10.92%). When RCV was divided by time interval, the detection rates were similar to prior rates in outpatients (0.19% ~ 1.34%). Using RCV multiplied by twice the upper limit of reference value as cutoff reduced the detection rate (0.07% ~ 1.58%). Conclusions: Reference change value is a robust criterion for delta check and included in clinical laboratory practice guideline. However, RCV‐based method generates high detection rates which increase workload. It needs modification for use in clinical laboratories. Abstract : Reference change value (RCV) can be used for determination of delta check limit. However, this study revealed that simple adaptation of RCV for delta check limit can produce excessive detection and increase the laboratory's workload. Further consideration and modification are needed for RCV and delta check before actually applying them to the clinical laboratory.